Data Acquisition with Multi-Way Wireless Communication via Ethernet - Mateus-Guerra, Tatiana; Pardo-Beainy, Camilo Ernesto; Rodríguez, Manuel Felipe (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2012)
This paper presents an innovative system that allows monitoring of variables associated with industrial processes, either remotely or locally, starting with a sensing of the variables, which performs the adaptation of sensors and signal conditioning and then make a step perform data acquisition and digital processing for displaying on an LCD, in turn making a protocol serial communication RS-232 and send data wirelessly via two-way RF modules, which communicate industrial process with a central computer that will monitor. Then the system involves a serial device server, tailoring the format of the data to Ethernet protocol allowing the process to be mounted on any network, and be monitored from anywhere via Ethernet through a graphical interface implemented in LabVIEW, creating a pleasant environment for creating graphical user behavior and data tables of the variables involved in theprocess. This system is widely applicable as it allows scalability and adaptation to any type of need in various environments such as industrial, agricultural, and environmental, among others.